Landlords, tenants and agrarian reform: local elites and regime transitions in Avis, Portugal, 1778-2011 - Almeida, M. A. P. de (Rural History, 2013)
In a small municipality in the Alentejo region of Portugal, the same group of families, defined by latifundia landownership or tenancy, dominated local political institutions for two centuries during which great changes occurred. Three revolutions resulted in regime transitions: the 1820 Liberal Revolution, the 1910 Republic and the 1926 Dictatorship, which led to Salazar’s Estado Novo. Even though a few members of these families offered some resistance to each one of these revolutions at an early stage, all of them adapted their behavior and kept local political control within their ranks. Local traditional institutions, such as the local council and the position of mayor, charitable and welfare associations, and corporative institutions created in the nineteen thirties and forties to direct economic activities, all of them were presided and controlled by members of the same rural elite. This is a fact until 1974, when the Carnation Revolution and the Agrarian Reform definitely removed and replaced these old elites with new ones. The Lords of the Land remained Lords of the Village for as long as the control over the main economic resource of the region was the major factor for political power. Land occupations were not permanent: the process was reversed due to political reasons related to Portugal’s adhesion to the EEC (EU) in 1986. Agrarian elites in Southern Portugal no longer control jobs nor the economy, therefore they no longer control local politics as they had done for several generations. The Carnation Revolution and the Agrarian Reform definitely removed and replaced old elites with new ones. The rural world is no longer based on agriculture as the main economic activity. Nature became a hiking ground or an all-terrain vehicles track. The future is elsewhere. And the present economic situation and lack of elites has transformed the rural world into a depopulated region.